2006
DOI: 10.1101/sqb.2006.71.018
|View full text |Cite
|
Sign up to set email alerts
|

Misexpression of the Caenorhabditis elegans miRNA let-7 Is Sufficient to Drive Developmental Programs

Abstract: The Caenorhabditis elegans microRNAs (miRNAs) lin-4 and let-7 promote transitions between stage-specific events in development by down-regulating the translation of their target genes. Expression of let-7 is required at the fourth larval stage for the proper transition from larval to differentiated, adult fates in the hypodermis; however, it was not known whether expression of let-7 is sufficient to specify these adult fates. To test this, we created fusion genes between lin-4 and let-7 that direct the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Studies manipulating let-7 expression have confirmed the essential role of let-7 in the transition from larval 4 stage to adult stage. Fusing the let-7 gene to the lin-4 gene and directing let-7 expression at larval stage 2 was shown to lead to precocious adult development at L4 stage, demonstrating that expression of let-7 is sufficient to specify adult fate in the worm (Hayes & Ruvkun 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies manipulating let-7 expression have confirmed the essential role of let-7 in the transition from larval 4 stage to adult stage. Fusing the let-7 gene to the lin-4 gene and directing let-7 expression at larval stage 2 was shown to lead to precocious adult development at L4 stage, demonstrating that expression of let-7 is sufficient to specify adult fate in the worm (Hayes & Ruvkun 2006).…”
Section: Introductionmentioning
confidence: 99%
“…11,36 Its essential role in this process was demonstrated by missexpressing let-7 at L2 and causing a precocious L4 transition in the worm. 49 If the model of reversed embryogenesis is correct, then an embryonic gene that is downregulated at the late stages of embryonic development would be expected to be one of the first genes that is reactivated during cancer development. Let-7 regulated genes are therefore good candidates for markers of early tumor progression.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…LIN-28 inhibits the biogenesis of the mature form of the let-7 microRNA (miRNA) (Newman et al, 2008;Piskounova et al, 2008;Van Wynsberghe et al, 2011;Viswanathan et al, 2008). When LIN-28 is downregulated, mature let-7 miRNA is produced, directing cells toward differentiated/adult fates (Copley et al, 2013;Hayes and Ruvkun, 2006;Rybak et al, 2008;Thornton and Gregory, 2012;Tsialikas and Romer-Seibert, 2015;Yu et al, 2007) by inhibiting the translation of primarily lin-41 and other target mRNAs (Ecsedi and Grosshans, 2013;Long et al, 2007;Slack et al, 2000;Vella et al, 2004a,b). homologs are proposed to silence the translation of target mRNAs (Ecsedi and Grosshans, 2013;Ecsedi et al, 2015;Loedige et al, 2013;Sonoda and Wharton, 2001;Vella et al, 2004a,b) that otherwise promote an undifferentiated/juvenile state (Chang et al, 2012;Ecsedi and Grosshans, 2013;Rybak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%